Reduced Compared With Traditional Schedules for Routine Antenatal Visits: A Systematic Review - Balk, Ethan M; Danilack, Valery A; Bhuma, Monika Reddy; Cao, Wangnan; Adam, Gaelen P; Konnyu, Kristin J; Peahl, Alex Friedman (Obstetrics and gynecology (New York. 1953), 2023)
To assess differences in maternal and child outcomes in studies comparing reduced routine antenatal visit schedules with traditional schedules. A search was conducted of PubMed, Cochrane databases, EMBASE, CINAHL, and ClinicalTrials.gov through February 12, 2022, searching for antenatal (prenatal) care, pregnancy, obstetrics, telemedicine, remote care, smartphones, telemonitoring, and related terms, as well as primary study designs. The search was restricted to high-income countries. Double independent screening was done in Abstrackr for studies comparing televisits and in-person routine antenatal care visits for maternal, child, health care utilization, and harm outcomes. Data were extracted into SRDRplus with review by a second researcher. Five randomized controlled trials and five nonrandomized comparative studies compared reduced routine antenatal visit schedules with traditional schedules. Studies did not find differences between schedules in gestational age at birth, likelihood of being small for gestational age, likelihood of a low Apgar score, likelihood of neonatal intensive care unit admission, maternal anxiety, likelihood of preterm birth, and likelihood of low birth weight. There was insufficient evidence for numerous prioritized outcomes of interest, including completion of the American College of Obstetricians and Gynecologists-recommended services and patient experience measures. The evidence base is limited and heterogeneous and allowed few specific conclusions. Reported outcomes included, for the most part, standard birth outcomes that do not have strong plausible biological connection to structural aspects of antenatal care. The evidence did not find negative effects of reduced routine antenatal visit schedules, which may support implementation of fewer routine antenatal visits. However, to enhance confidence in this conclusion, future research is needed, particularly research that includes outcomes of most importance and relevance to changing antenatal care visits. PROSPERO, CRD42021272287.